Finite Element Analysis of the effect of High Tibial Osteotomy correction angle on articular cartilage loading - Zahra Trad (2018)
Osteoarthritis is a globally common disease that imposes a considerable ongoing health and economic burden on the socioeconomic system. As more and more biomechanical factors have been explored, malalignment of the lower limb has been found to influence the load distribution across the articular surface of the knee joint substantially. In this work, a three-dimensional finite element analysis was carried out to investigate the effect of varying the high tibial osteotomy correction angle on the stress distribution in both compartments of the human knee joint. Thereafter, determine the optimal correction angle to achieve a balanced loading between these two compartments. The developed finite element model was validated against experimental and numerical results. The findings of this work suggest that by changing the correction angle from 0 degrees to 10 degrees valgus, high tibial osteotomy shifted the mechanical load from the affected medial compartment to the lateral compartment with intact cartilage. The Von Mises and the shear stresses decreased in the medial compartment and increased in the lateral compartment. Moreover, a balanced stress distribution between the two compartments as well as the desired alignment were achieved under a valgus hypercorrection of 4.5 degrees that significantly unloads the medial compartment, loads the lateral compartment and arrests the progression of osteoarthritis. After comparing the achieved results against the ones of previous studies that explored the effects of the high tibial osteotomy correction angle on either clinical outcomes or biomechanical outcomes, one can conclude that the findings of this study agree well with the related clinical data and recommendations found in the literature.